Genome-wide identification of TBL gene family and functional analysis of GhTBL84 under cold stress in cotton - Zhu, Xiaoqing; Ma, Xiaowei; Hu, Wanying; Xing, Yulin; Huang, Shengcai; Chen, Zequan; Fang, Lei (Frontiers in Plant Science, 2024)
Cotton fiber, the mainstay of the world's textile industry, is formed by the differentiation of epidermal cells on the outer peridium of the ovule. The TBL gene family is involved in the regulation of epidermal hair development as well as response to abiotic stress. However, the function of TBL genes in cotton has not been systematically studied yet. Here, we identified 131 and 130 TBL genes in TM-1 (typical of Gossypium hirsutum) and Hai7124 (typical of Gossypium barbadense), respectively. Phylogenetic, gene structure, expression pattern and cis-element of promoter analysis were performed and compared. Single gene association analysis indicated that more TBL genes related to fiber quality traits were found in G. barbadense, whereas more genes associated with yield traits were found in G. hirsutum. One gene, GhTBL84 (GH_D04G0930), was induced by treatment at 4 ℃ for 12 and 24 h in G. hirsutum and silencing of the GhTBL84 gene by VIGS technology in TM-1 can significantly improve the resistance of cotton seedlings to low temperature stress. CollectivelyIn sum, our study conducted a genome-wide identification and comparative analysis of TBL family genes in G. hirsutum and G. barbadense and demonstrated a group of TBL genes significantly associated with fiber quality and excavated cold stress responsive gene, such as GhTBL84, providing a theoretical basis for further improving cotton agronomic traits.